An unusual termination of facial vein and anterior division of retromandibular vein into external jugular vein: a case report. - Jyothsna P; Naveen K; Mohandas Rao KG; Ashwini LS; Somayaji SN; Satheesha Nayak B (Department of Surgery, UKM Medical Centre, 2014)
Facial vein, being the largest vein of the face forms the common facial vein after joining with the anterior division of retromandibular vein below the angle of the mandible. Usually, it drains into the internal jugular vein. During routine dissection of head and neck region of a male cadaver, aged approximately 50 years, an unusual pattern in the termination of veins on the left side of the neck was observed. The formation, course and termination of external jugular vein were normal. The anterior division of retromandibular vein joined with external jugular vein about 5 cm above the clavicle and the facial vein opened into the external jugular vein about 2.5 cm above the clavicle. In addition, there was a thin venous communication between anterior division of retromandibular vein and external jugular vein. The superficial veins of the neck are often used for cannulation; either for intravenous infusion or for central venous pressure monitoring. Furthermore, these venous segments are used as a patch for carotid endarterectomies. Hence, a thorough knowledge of the normal anatomy and their variations may be useful for performing these procedures.